SPECIFIC FEATURES OF THE FORMATION OF KNOWLEDGE IN NATURAL SCIENCES IN THE WORLD EDUCATION SYSTEM - Oripov Shokhrukh Ilkhom oglu (Western European Studies, 2025)
The article discusses the history of the development of knowledge about nature and natural sciences, in particular about biodiversity, the emergence of biodiversity in the first place, that is, its evolution. In addition, the article presents ideas on the content and essence of the concept of biodiversity, the teaching of natural sciences based on world experience, including the educational systems of developed countries such as America, Japan and European countries, the order and features of the teaching of lessons in primary grades.
Keywords: biodiversity; nature; natural sciences; worldview